2004
DOI: 10.2139/ssrn.555834
|View full text |Cite
|
Sign up to set email alerts
|

Credibility and Adjustment: Gold Standards Versus Currency Boards

Abstract: It is often maintained that currency boards (CBs) and gold standards (GSs) are alike in that they are stringent monetary rules, the two basic features of which are high credibility of monetary authorities and the existence of automatic adjustment (non discretionary) mechanism. This article includes a comparative analysis of these two types of regimes both from the perspective of the sources and mechanisms of generating confidence and credibility, and the elements of operation of the automatic adjustment mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Indeed, Blackburn and Christensen (1989, p.4) argued that: 'In general, credibility of monetary policy will depend not just upon monetary policy alone but rather upon the perceived coherence of the overall macroeconomic program, together with the intellectual and political consensus on the economic theory being used and the objectives and conduct of economic policy.' Desquilbet and Nenovsky (2007) argued that in CBA countries a source of trust in the local currency is trust in the anchor currency (in our case the euro). Therefore, we control for the effect of trust in the anchor currency, by using answers to another question from the survey: 'Over the next five years, the euro will be a very stable and trustworthy currency'.…”
Section: Insert Figure 1 Around Herementioning
confidence: 89%
See 1 more Smart Citation
“…Indeed, Blackburn and Christensen (1989, p.4) argued that: 'In general, credibility of monetary policy will depend not just upon monetary policy alone but rather upon the perceived coherence of the overall macroeconomic program, together with the intellectual and political consensus on the economic theory being used and the objectives and conduct of economic policy.' Desquilbet and Nenovsky (2007) argued that in CBA countries a source of trust in the local currency is trust in the anchor currency (in our case the euro). Therefore, we control for the effect of trust in the anchor currency, by using answers to another question from the survey: 'Over the next five years, the euro will be a very stable and trustworthy currency'.…”
Section: Insert Figure 1 Around Herementioning
confidence: 89%
“…However, other things being equal, these expectations are likely to be firmer in countries with a CBA since it is harder to deviate from a fixed rate as the (fixed exchange rate) rule is embedded in law and the costs of changing legislation are argued to be high. However, achievement of a high level of credibility of the monetary authority under a CBA is not automatic, since sustaining credibility depends on the state of the economy (Drazen and Masson, 1994) and the specific (political/institutional) circumstances in the country (Blackburn and Christensen, 1989;Desquilbet and Nenovsky, 2007).…”
Section: Credibility Of a Cbamentioning
confidence: 99%
“…Bulgaria's CBA is heavily debated in economic literature (Avramov, 1999;Carlson & Valev, 2001;Chobanov & Nenovsky, 2004;Desquilbet & Nenovsky, 2004;Dobrev, 1999;Fabris & Rodic, 2013;Hardouvelis & Monokrousos, 2009;Hristov, 2004;Ialzanov & Nenovsky, 2001;Marinova, 2016;Miller, 1999;Minassian, 2018;Moheeput, 2008;Nenovsky & Dimitrova, 2002;Nenovsky, Hristov & Mihaylov, 2002;Todorov, 2013). Hanke and Schuler (1991) suggested that a currency board be introduced in Bulgaria in order to achieve a convertibility of the Bulgarian lev into foreign currency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hristov concluded that conditions for an effective discretionary monetary policy of a classical central bank in Bulgaria during the period 1997-2004 did not exist for two reasons: first, the economic dynamics during this period was determined mainly by structural rather than by cyclical factors and second, there is no confidence of economic agents in discretionary monetary policy. Desquilbet and Nenovsky (2004) compared the Gold Standard and the Currency Board as monetary regimes with a high degree of confidence in monetary authorities and an automatic adjustment mechanism. The authors made two important conclusions: first, the credibility of the Gold Standard was determined by endogenous factors, and in the currency board by exogenous factors, and second, asymmetries in economic adjustment are much higher in the currency board than in the Gold Standard.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation